(untitled) (Journal of Environmental Microbiology and Toxicology, 2021)
Alkaline cellulase producing Fusarium oxysporum VSTPDK was isolated and screened from the soil of Kapurthala district Punjab, India. This organism produced endoglucanase (CMCase) and exoglucanase (FPase) when grown at a different range of parameters pH (6, 7, 8, 9, 10 and 11), temperature (30, 40, 50 and 60OC), incubation time (4th 6th 8th 10th and 12th day) and nitrogen source (NH4SO4, NH4Cl, NaNO3 and NH4HCO3). Carboxymethylcellulose (CMC) and cellulose powder were used as the sole carbon source. In this research, statistical tools called Response Surface Methodology (RSM) was used for the optimization of cellulase enzyme by selecting three important parameters after one factor at a time (OFAT) approach. Using OFAT, optimum production of both CMCsase (3.52U/mL) and FPase (4.07U/mL) were achieved after 8 days incubation at pH 8, temperature 30OC and 1.0g/L ammonium sulphate while RSM produced CMCase 3.91U/mL and FPase 4.26U/mL respectively when incubated for 8 days at pH 8.5, temperature 45 and 3% ammonium sulphate concentration. Optimization of the culture conditions using RSM leads to an increase of 0.39U/mL (CMCase) and 0.19U/mL (FPase). The use of RSM has gained considerable attention in the past decade in the optimization of various physicochemical parameters and nutritional factors. Its application in different industries may find ways of selecting different factors influencing cellulase activity. The fungus can produce a considerable amount of cellulase enzyme at a pH of up to 10 and 50OC. To our knowledge, this is the first report of alkalothermophilic oxysporum VSTPDK from Punjab, India.